2012
DOI: 10.1007/s10103-012-1239-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potassium binoxalate gel and Nd:YAG laser in the management of dentinal hypersensitivity: a split-mouth clinical and ESEM study

Abstract: Dentinal hypersensitivity is one of the oldest recorded complaints of discomfort to mankind and yet there appears to be no permanent treatment for this clinical condition. This study was designed to evaluate the clinical efficacy of potassium binoxalate gel and neodymium:yttrium-aluminum-garnet (Nd:YAG) laser on dentin hypersensitivity for a period of 9 months. Eighty teeth (20 subjects, 25-55 years old, M = F) were evaluated in a split-mouth design to receive potassium binoxalate (group A, 40 teeth) and Nd:YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
0
26
0
5
Order By: Relevance
“…Currently, many strategies have been developed to deal with DH. For example, calcium-phosphate 5) , potassium oxalate 6) , bioactive glasses 7) , fluoride 8) , and other materials have been used either in dentifrices or as single or multiple application agents to occlude dentinal tubules. However, there are no single desensitizing agent that can be considered ideal for this condition, since these materials have difficulties in replicating the hierarchical structure of mineral within the collagen matrix and do not fit well with natural dentin tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many strategies have been developed to deal with DH. For example, calcium-phosphate 5) , potassium oxalate 6) , bioactive glasses 7) , fluoride 8) , and other materials have been used either in dentifrices or as single or multiple application agents to occlude dentinal tubules. However, there are no single desensitizing agent that can be considered ideal for this condition, since these materials have difficulties in replicating the hierarchical structure of mineral within the collagen matrix and do not fit well with natural dentin tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Laser treatment has also been recommended for treatment of DH. Studies have reported that the neodymium: yttrium-aluminum-garnet (YAG) laser, the erbium:YAG laser and galium-aluminium-arsenide low level laser all reduce DH [45][46][47]. A more recent literature review on the use of lasers in treatment of DH has suggested that though it has a slight clinical advantage over topical medicaments, further studies with larger samplesizes, long-term, high-quality randomised controlled clinical trials are needed before definitive conclusions can be made [48].…”
Section: In-office Treatmentmentioning
confidence: 99%
“…Um dente com dentina mais transparente absorve menos radiação pelo laser de Nd:YAG do que uma dentina com pigmentações marrons ou mais amareladas 14,28 . Para que o laser produza os efeitos desejáveis e para evitar danos térmicos, a irradiação deverá ser realizada com potências inferiores a 1,5W, pois valores superiores podem causar danos térmicos indesejáveis no tecido alvo, como rachaduras e carbonização, e na polpa dental 12,14,28 . Outros lasers bastante utilizados para o tratamento da hipersensibilidade dentinária são os lasers de érbio (Er:YAG e Er,Cr:YSGG) e CO 2 , que atuam de forma semelhante na dentina.…”
Section: Laser De Baixa Intensidadeunclassified
“…Talesara et al 28 estudaram a eficácia clínica de um gel a base de oxalato de potássio e do laser Nd: YAG para o tratamento da hipersensibilidade dentinária hipersensibilidade dentinária, durante um período de 9 meses. Após o tratamento de 20 pacientes de ambos os sexos, os autores concluíram que os dois tratamentos propostos foram efetivos para eliminar o desconforto dos pacientes imediatamente após a aplicação dos métodos citados.…”
Section: Laser Alta Intensidadeunclassified
See 1 more Smart Citation